Sailing : philosophy for everyone : catching the drift of why we sail - Goold, Patrick Allen (Chichester [UK] ; Malden, MA : Wiley-Blackwell, 2012)
"This volume reveals the wisdom we can learn from sailing, a sport that pits human skills against the elements, tests the mettle and is a rich source of valuable lessons in life. Unravels the philosophical mysteries behind one of the oldest organized human activities Features contributions from philosophers and academics as well as from sailors themselves Enriches appreciation of the sport by probing its meaning and value Brings to life the many applications of philosophy to sailing and the profound lessons it can teach us A thought-provoking read for sailors and philosophers alike "--
"This volume reveals the wisdom we can learn from sailing, a sport that pits human skills against the elements, tests the mettle and is a rich source of valuable lessons in life"--
Includes bibliographical references and index.
Keywords: Sailing -- Philosophy; Philosophy -- Popular works; SPORTS & RECREATION -- Sailing; Electronic books